Educação física escolar e material didático: construção e uso de livro paradidático digital e interativo - Cunha, Sérgio Melo da (2022)
The present study starts from the relationship between Physical Education (PE) at school and the use of teaching materials, considering the historical relevance of this theme for the curricular component. It is under this excitement that our research is developed, questioning the possibility of implanting an unusual artifact to the school PE tradition - the paradidactic book - in the teaching of themes that allow the transversalization with all the thematic units of the discipline in the National Common Curricular Base (BNCC), in the case of health. It seeks to answer the following question: how does the construction process take place, as well as the didactic-pedagogical steps in school Physical Education from the use of the digital and interactive paradidactic book? The study's general objective is to understand the strategies of PE teachers and elementary school II teachers to enable the use of digital and interactive teaching material. This is a qualitative and descriptive research. The study is developed in three stages. The first exposes the process of idealization, writing and presentation of a digital and interactive paradidactic book. The second presents the contact with PE teachers from the public education network in the city of Natal/RN. While the third stage deals with a content analysis on the data collected from the focus group of teachers from the municipal public education network in the capital of Rio Grande do Norte (planning, classes, and semi-structured interviews). The group is made up of four teachers and a teacher who will be presented in the text as fictional characters from the Star Wars universe. Of these, two used the paradidactic book in their practice. One gave the material the guiding character of his classes, while another made use of the artifact as a complement to the content presented. The other teachers pointed out the lack of accessibility and the context of remote teaching as the main factors for preventing the use of the material.